Swearing Produced by The Shelby Family in The Series Peaky Blinders - Aptanta Faiz; I Made Suastra; Made Detriasmita Saientisna (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Swearing is the primary notion in this study. There are two objectives of this study, which are to classify the types of swearing in the series and categorize their motive. Swearing, in all its forms, has historically been both revered and reviled. It can serve as a cathartic release of emotion, a vehicle for rebellion against societal norms, or a sharp tool for emphasis. The analysis was conducted based on the theories proposed by Pinker (2007) and Stapleton (2003). Battistela (2005) differentiated swearing into 5 categories; Dysphemistic, Abusive, Idiomatic, Emphatic, Cathartic. Stapleton (2003) formulated the motives of swearing into nine types: story-telling, emphasis, anger/tension release, habit, normality, intimacy, vulnerability, part of personality, a way to shock. The analyzed data taken from a TV series Peaky Blinders. The collected data is analyzed by using the descriptive qualitative method since it did not involve any numerical data. Through the analysis, the use of swearing in a speech is revealed that the background of the character contributes to the family characteristics, in which it can affect their verbal aptitude and attitude, whether they will be good or bad. The Shelby family mostly swear because of the need to release or express their anger caused by the problems that they are facing on a daily basis and it is almost impossible for them to not express their emotions and anger in a form of swearing.